Pyranocoumarins from the twigs of Mammea siamensis - Vilailak Prachyawarakorn (2018)
Four unusual pyranocoumarins (1-4) have been isolated from the dried twigs of M. siamensis. The structures were determined by spectroscopic data, especially 1D and 2D NMR experiments. © 2006 Elsevier Ltd. All rights reserved.